A prospective study of the study of maternal and perinatal outcome in cases of eclampsia - Ponde, Sanjay Ravan; Hatkar, Preeti; Nandanwar, Y. S.; Chavan, Niranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: This is an observational analytical study carried out in the department of obstetrics and gynecology, in a tertiary care center to determine the factors influencing fetal and maternal outcome, prognosis and complications in booked and unbooked eclamptic cases. Methods: The present study is a prospective study of perinatal and maternal outcome in 50 cases of eclampsia, above 32 weeks of gestation, from 1st May 2013 to 30th April 2014. Patients with medical complications like anemia, preexisting hypertension, diabetes, vascular or renal disease, multiple gestation, polyhydraminos, etc. are excluded from the study. Detailed history, physical examinations were carried out and appropriate management instituted as per individual patient need. Follow-up of mothers up to 6weeks postpartum and neonates in the early neonatal period was done. Results: Incidence of eclampsia is 0.64%, incidence of maternal mortality is 0.4% and perinatal mortality is 24%. 36% of patients developed complications. Maternal mortality was significantly high in patients with 6 or more episodes of convulsions. The most common cause of perinatal mortality is prematurity. Antepartum eclampsia with gestational age less than 36 weeks, BP >160/100, preterm births, low birth weight babies, low apgar scores influenced adverse perinatal outcome. Conclusions: Eclampsia still remains a major problem in developing countries. It is one of the important causes of maternal and perinatal morbidity and mortality due to lack of proper ANC, low socio-economic status and lack of education.